2021
DOI: 10.3855/jidc.12326
|View full text |Cite
|
Sign up to set email alerts
|

Late onset periprosthetic joint infection of the knee caused by Streptococcus anginosus. Case presentation and literature review

Abstract: Periprosthetic joint infection (PJI) is one of the most dramatic complications of joint arthroplasty. Although streptococcal bone and joint infections are less common than staphylococcal cases, their role as causative agents of bone and joint remains significant accounting for at least 10% of PJIs. Streptococcus anginosus group (SAG) bacteria are usually found in the normal flora of the urogenital tract, intestinal tract and oropharynx and could cause pyogenic infections to affect brain, lungs and liver. SAG b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several studies have reported cases of late-onset PJIs caused by oral streptococci, often in the setting of dental procedures or poor oral hygiene [12][13][14]17,18,[21][22][23]. A systematic review by Moreira et al found limited evidence to support the use of antibiotic prophylaxis in patients with periodontitis undergoing joint arthroplasty [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported cases of late-onset PJIs caused by oral streptococci, often in the setting of dental procedures or poor oral hygiene [12][13][14]17,18,[21][22][23]. A systematic review by Moreira et al found limited evidence to support the use of antibiotic prophylaxis in patients with periodontitis undergoing joint arthroplasty [6].…”
Section: Discussionmentioning
confidence: 99%
“…Marongiu reported a case in which a 72-year-old male had a late onset of PJIs due to Streptococcus anginosus . The infection was treated through two-stage revision arthroplasty and postoperative antibiotic therapy (vancomycin and levofloxacin) [ 18 ]. Several previous studies regarding streptococcal prosthetic joint infections (PJIs) are reviewed and summarized in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…19 A patient of periprosthetic knee infection caused by Streptococcus anginosus, was successfully treated by vancomycin (1 g, q12h, iv) and levofloxacin (750 mg, qd, iv) for 4 weeks, and then levofloxacin (750 mg, qd, po) for 2 weeks. 54 In 2020, Eloy et al 55 developed a PPK model of levofloxacin with 59 OAI patients, and the model consisted of a one-compartment model with first-order absorption and elimination. Monte Carlo simulations evaluated the PTA of levofloxacin at a dose of 750 mg, qd, with different ages and renal functions.…”
Section: Fluoroquinolonementioning
confidence: 99%